1994
DOI: 10.1172/jci117211
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by interferon-gamma of human mononuclear cell-mediated low density lipoprotein oxidation. Participation of tryptophan metabolism along the kynurenine pathway.

Abstract: In this study we examined the potential inhibition by interferon-y (IFN'y) of the early stages of low density lipoprotein (LDL) oxidation mediated by human peripheral blood mononuclear cells (PBMC) and monocyte-derived macrophages (NMDMN) in Ham's F-10 medium supplemented with physiological amounts of L-tryptophan (Trp). We assessed LDL oxidation by measuring the consumption of LDL's major antioxidant (i.e., a-tocopherol) and targets for oxidation (cholesteryllinoleate and cholesterylarachidonate), together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 57 publications
3
62
0
Order By: Relevance
“…7B, such treatment did not decrease IDO activity. Similar results were observed with rhIFN␥-primed human monocyte-derived macrophages (data not shown) and peripheral blood mononuclear cells (18), where diphenyleneiodonium at concentrations up to 20 M did not modulate IDO activity.…”
Section: Figure 5 Mn-tbap Does Not Decrease Ido Activity In Rhifn␥-psupporting
confidence: 86%
See 1 more Smart Citation
“…7B, such treatment did not decrease IDO activity. Similar results were observed with rhIFN␥-primed human monocyte-derived macrophages (data not shown) and peripheral blood mononuclear cells (18), where diphenyleneiodonium at concentrations up to 20 M did not modulate IDO activity.…”
Section: Figure 5 Mn-tbap Does Not Decrease Ido Activity In Rhifn␥-psupporting
confidence: 86%
“…to reductively activate purified rabbit IDO such that L-Trp and O 2 can bind tightly (9). Furthermore, using 18 O 2 -labeled potassium superoxide, these authors showed O 2 .…”
mentioning
confidence: 96%
“…Laccase and ceruloplasmin have previously been shown to oxidize many of the same substrates [22]. Because 3-HAA oxidation has been reported to play an important physiological role in mammals [1,5], we tested the ability of ceruloplasmin to catalyze CA formation. Oxidation of 3-HAA by ceruloplasmin was slower than for the laccase-mediated reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of 3-HAA to CA has received considerable attention in clinical studies because 3-HAA is produced in relatively large amounts by interferon-y-primed mononuclear phagocytes [5] and has been shown to act as a powerful scavenger of reactive oxygen species [1]. CA is one of the major products of the peroxyl radical-mediated oxidation of 3-HAA suggested to prevent oxidative damage in mammalian tissues [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of LDL by cultured mouse peritoneal macrophages, as defined by the content of thiobarbituric acid-reacting substances, is decreased by incubating cells with interferon (IFN)-␥ (15). One potential mechanism of IFN-␥ -induced reduction of LDL oxidation is an acceleration of extracellular tryptophan degradation (16). Several reports have demonstrated a role of IFN-␥ via a lipoxygenase pathway that is also thought to involve oxidation (17).…”
Section: Cytokine Regulation Of Macrophage-mediated Lipoprotein Modifmentioning
confidence: 99%